(untitled) (Reflection and Critique Law Magazine, 2020)
The objective of this article is to rethink the construction of Human Rights in the context of modernity and its relation with Islamic Human Rights. Demonstrating that the dream of human rights as universals has fueled illusions for a long time and turned into a nightmare in the period of solid modernity. With the crisis of modernity, human rights developed in an increasingly plural and diverse world, as under the Islamic perspective of human rights. Facing this situation through open, frank and transparent dialogue in a different environment from the first moment of modernity, called liquid modernity by Zygmunt Bauman.